Association of inflammatory genes in obstructive sleep apnea and non alcoholic fatty liver disease in Asian Indians residing in north India - Bhatt, Surya Prakash; Guleria, Randeep; Vikram, Naval K.; Nandhan, S. V.; Singh, Yogendra; Gupta, A. K. (PloS one, 2018)
Previous studies have indicated that variants of the high sensitive C-reactive protein (CRP), Interleukin (IL)-6 and leptin receptor (LEPR) genes are associated with the presence of obstructive sleep apnea (OSA) but not in non-alcoholic fatty liver disease (NAFLD) in Asian Indians. The study was conducted to investigate the association of CRP rs1130864 (1444C/T), IL-6 rs1800795 (-174G/C) and LEPR rs1137101 (Q223R) genes with OSA and NAFLD in Asian Indians residing in North India. 240 overweight/ obese subjects [body mass index (BMI>23kg/m2)], 124 with OSA and with NAFLD (group 1), 47 with OSA without NAFLD (group 2), 44 without OSA and with NAFLD (group 3) and 25 without OSA and without NAFLD (group 4) were recruited in this study. The severity of NAFLD was based on abdomen liver ultrasound and of OSA on overnight polysomnography. Clinical details, anthropometry profile, body composition, biochemical parameters and inflammatory markers were measured. Polymerase chain reaction and restriction fragment length polymorphism of CRP, IL-6 and LEPR gene was performed. The associations of these polymorphisms with clinical, anthropometric and biochemical profiles were investigated. The genotypes were confirmed by DNA sequencing analysis. The C, T and R alleles of IL-6, CRP and LEPR genes was more frequent in OSA and NAFLD subjects and significantly correlated with higher protein levels. The prevalence of variant genotypes C/T of CRP, G/C of IL-6 and Q/R of LEPR genes was significantly higher in OSA subjects as compared to non OSA subjects. Further, C/C genotype of IL-6 (G/C), T/T of CRP (C/T) and RR genotype of LEPR (Q/R) was associated with significantly higher BMI, fat mass (kg), % body fat, waist circumference, serum triglycerides, total cholesterol, alkaline phosphate, aspartate transaminase and fasting insulin levels in OSA and NAFLD subjects. Using a multivariate analysis, the combined effect of three polymorphisms of CRP, IL-6 and LEPR gene variants on OSA and NAFLD risk was evaluated. Odds ratio for OSA and NAFLD with the combination of the three gene polymorphisms increased to 2.84 (95% CI: 1.08-6.54; p = 0.04) even when adjusted for sex, age and BMI. Polymorphisms of pro-inflammatory cytokine genes were associated with increased risk of OSA and NAFLD in Asian Indians.